FACTORS AFFECTING THE PROFESSIONALISM OF NON-CLINICAL STAFF AT SAIFUL ANWAR GENERAL HOSPITAL, EAST JAVA PROVINCE - R. Henggar Sulistiarto; Hariyanti, Tita; Rahmani Ratri, Devita (Universitas Brawijaya, 2025)
The professionalism of non-healthcare staff plays a vital role in hospital health services. Their professional conduct contributes to the key service quality indicators of tangibles, reliability, responsiveness, assurance, and empathy, thus affecting the overall quality of healthcare services provided to the public. This study aims to analyze the factors influencing the professionalism of non-healthcare personnel at Dr. Saiful Anwar General Hospital (RSSA). Employing an explanatory research design, the study uses quantitative analysis to examine the effects of employment status, remuneration, and promotion opportunities on staff professionalism. Data were collected through a questionnaire distributed to 281 non-healthcare staff at RSSA and were analyzed using logistic regression. The results indicated that employment status did not significantly affect professionalism (t = 2.938, p = 0.087). In contrast, remuneration (t = 7.586, p = 0.006, B = 0.913) and promotion opportunities (t = 8.211, p = 0.004, B = 0.907) both had a significant positive impact. Collectively, these three factors significantly influenced the professionalism of non-healthcare staff (F = 19.007 > 3.08285; p = 0.000 < 0.05). The findings highlighted the importance for healthcare organizations to prioritize fair compensation structures and clear career advancement pathways to enhance employee morale and service quality. Effective management of these factors is expected to foster higher levels of professionalism, which in turn improves healthcare service quality, patient satisfaction, and operational efficiency.